Effect of nano-calcium carbonate on resistance to calcium leaching and chloride penetration in recycled concrete - Jian-Hua Jiang; Si-Qi Zhao; Xiao-Zhe Shi; Rui-Qi Xia; Huang-Xin Zhang (European Journal of Environmental and Civil Engineering, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Study on the O2 migration pathway and critical product formation mechanism in the water immersion coal oxidation - Guo-yu Shi; Xin-xiao Lu; Guan Wang; Zhao Yang; Long He; Rui-nan Zhang (Fuel, 2026)

Managing nitrate pollution in mixed land-use watersheds: source attribution and removal revealed by isotopes and 15N pairing - Jian Zhang; Hao Jiang; Yanping Li; Wenshi Zhang; Wenlu Lan; Junlin Shu; Xin Luo; Rui Zhang; Ke Pan (Ecological Engineering, 2026)

One-step simultaneous PO43− doping and Li3PO4 coating of LiMn2O4 for enhanced stability and Li+ selectivity in lithium extraction from low-grade salt lake brines with high Mg2+/Li+ ratios - Chen Zhao; Xin Zhang; Zihua Li; Shuang Liu; Yupeng Wang; Lei Wang; Rui Miao (Desalination, 2026)

Biodiversity and paleoenvironmental reconstruction of the Jehol Biota in the Jiufengshan Formation of eastern Inner Mongolia, northeastern China - Yan Xue; Zhenhua Jing; Xiao Teng; Xin Zhang; Peihan Liu; Siyu Song; Rui Fang; Gang Li; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Enhanced stability of CH3NH3PbBr3 quantum dots for electrochemiluminescence detection of saxitoxin - Yu Han; Ting Zhang; Rui Kang; Xin Gao; Jiawei Liu; Qingchun Yin; Hongmei Cao; Long Wu (Food Chemistry, 2026)

From charge dependence to host-guest recognition: A reliable CZE method for simultaneous separation and determination of flavonoid glycosides with similar structures - Rui Zhang; Biying Guo; Xin Zhou; Fuyu Yang; Yong Xu (Food Chemistry, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Outer-rise serpentinization water flux: a fault-localized mechanism with nonlinear controls - Rui Zhang; Jianfeng Yang; Chang Zhang; Tong Liu; Linpei Deng; Xin Wang; Liang Zhao (Earth and Planetary Science Letters, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Oxygen-vacancy-mediated BrO3− electroreduction: Positively charged microenvironment enables directional diffusion and spontaneous adsorption - Xiangbin Huang; Yue Cheng; Zhipeng Luo; Ruiqi Zheng; Yangying Zhao; Salman Farissi; Rui Liu; Gong Zhang; Xin Yu; Huabin Zeng (Chemical Engineering Journal, 2026)

CRISPR-programmable nanoparticle transport in salt-gated porous media for visual DNA detection - Kurt T. Schalper; Rui Yang; Xin Guan; Jiongyu Zhang; Chengyu Hou; Xingye Liu; Minjie Pei; Trystin Cote; Yupeng Chen; Changchun Liu (Chemical Engineering Journal, 2026)

Transparent, bio-based dielectric films with ultrahigh breakdown strength fabricated from hydrogen-bonded cellulose acetate and tannic acid for energy storage - Rui Luo; Xin-rui Xiao; Zhe-hao Kang; Chao-qun Wu; Ting Huang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Microplastic pollution in an anthropogenically modified river: sediment occurrence, associated microbiota, and environmental correlates - Kai Zhang; Ge Ma; Qingyi Wang; Chengshi Ding; Xinlu Shen; Chaoyue Zhao; Siwei Gao; Chenyang Shen; Hui Gao; Rui Xin; Fengxia Yang (Environmental Monitoring and Assessment, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Influence of water content on multi-component shale gas exploitation and CO2 sequestration in illite nanopores - Tao Wang; Yinbang Zhou; Rui Wang; Zhichao Zhang; Liehui Zhang; Yulong Zhao; Xin Chen (Fuel, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Recent advances in electromechanical coupling functional metamaterials - Han Yan; Yi Zhang; Wei Zhong Jiang; Xiao Ji; Rui Zhu; Jing Bo Sun; Yi Min Xie; Ken E. Evans; Xin Ren (Engineering Structures, 2026)

Pore-scale investigation of pore structure characteristics and their impact on thermo-hydraulic coupled transport in unsaturated bentonite: From fractal reconstruction to direct numerical simulation - Guangchang Yang; Xin Gong; Bo Zhang; Rui Zhou; Yang Liu; Bing Bai (Computers and Geotechnics, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Polymer-based hydrogen barrier coatings: Material design, mechanisms, and theoretical simulation - Zhuofan Li; Zhibin Chen; Lingwei Ma; Jinke Wang; Xin Guo; Rui Tian; Bowei Zhang; Huaiyuan Wang; Dawei Zhang (Chemical Engineering Journal, 2026)

Mesoporous carbon nanospheres-confined ZnMn2O4/Mn3O4 heterostructures for sustainable zinc-ion storage - Ling-Xin Kong; Songtao Zhang; Yaxun Hu; Peng Liu; Wanchang Feng; Zefan Sang; Xiaotian Guo; Hao Gong; Rui Wang; Dae Joon Kang; Huan Pang (Chemical Engineering Journal, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Introducing Phoebe bournei into Chinese fir plantations reshapes soil nutrient conditions and microbial processes along a mixing chronosequence - Xin Guan; Rui Chen; Xiang Zheng; Wenqi Zhang; Xiaopeng Shuai; Jiang Jiang (Plant and Soil, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

Evaluation of microplastic removal performance and technologies in secondary effluent from typical sewage treatment processes using a self-developed enrichment–purification–separation-integrated device - Wenjuan Zhang; Xin Zhang; Li Fan; Siyu Wang; Shuang Ge; Rui Miao; Lei Wang; Yongtao Lv (Process Safety and Environmental Protection, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Mechanistic study on direct oxidation of xylose to xylonic and xylaric acids in base-free medium - Yinghao Wang; Wei Yu; Zhaozhe Li; Rui Min; Wenmao Zhang; Chunmei Li; Feng Du; Wenjuan Yan; Xin Jin; Chaohe Yang (Chemical Engineering Journal, 2026)

Advancing PCOS drug development: multi-omics discovery of key targets and repurposable compounds - Zhiyong Xiao; Xin Zhang; Yuxin Zhang; Jiajia Liu; Xiaoyan Zheng; Rui Lai; Han Yang; Jie Wu; Jie Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Computational Fracture Mechanics Modeling and Multivariate Analysis of Mixed-Mode I-II Crack Propagation in Unstable Rock Masses - Shikuo Chen; Rui Wang; Yifan Hou; Zhiming Wang; Xin Pan; Yang Zhang; Xiaoyan Zhao; Minghao Chen; Hang Zhou; Zhewei Wang (Rock Mechanics and Rock Engineering, 2026)

Prevotella copri impairs bone mass via osteoclast activation in mice - Rui Li; Haiyan Zhang; Shiyong Xin; Tiantian Zeng; Wenchu Qian; Yawen Sun; Yunfei Cao; Yuxin Wang; Bin Li; Ming Tian; Hai Lin; Haifang Li (Molecular and Cellular Biochemistry, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Invasive giant African snails as potential reservoirs of antimicrobial resistance and bacterial pathogens in urban park - Yiyue Zhang; Zhonghui Tang; Huayuan Shangguan; Rui Zhu; An Xie; Qiansheng Huang; Jianqiang Su; Patrick O'Connor; Yong Jiang; Xin Sun (Journal of Environmental Management, 2026)

Amelioration of obesity-induced endothelial dysfunction by a synthetic ocean-derived peptide via regulating PPARα/γ pathway - Tiantian Zhou; Xinyi Chen; Yuehan Wang; Xutao Zhang; Lingchao Miao; Rui Tian; Yumeng Li; Yingying Feng; Xin Wu; Wai San Cheang (Food Research International, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

A tropical fermented-food-derived Lactiplantibacillus plantarum SP055 alleviates DSS-induced colitis through coordinated regulation of gut microbiota and intestinal barrier function - Jianwei Zang; Yibo Shi; Xiaotong Hao; Xia Fan; Yimeng Kou; Wanxiang Zhang; Luyao Xiao; Chang Xu; Tao Lin; Xin Rui; Dan Gan; Wei Li (Food Bioscience, 2026)

Polyvinylpyrrolidone-enhanced terahertz metamaterials for room-temperature, trace VOC detection and discrimination - Rui Zhang; Lanju Liang; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun; Jie Huang (Chemical Engineering Journal, 2026)

High transparent, high strength and high energy storage capability of cellulose triacetate films via incorporating cellulose nanocrystal - Xin-rui Xiao; Rui Luo; Jing-hui Yang; Nan Zhang; Yong Wang (Carbohydrate Polymers, 2026)

From addition to regulation: Lactic acid bacteria-driven interfacial mechanisms and spatial control in food bioactive packaging - Jianwei Zang; Yan Luo; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Luyao Xiao; Xin Rui; et al. (Trends in Food Science & Technology, 2026)

Bioaerosol multi-pollutant source localization in urban microclimates using an improved particle swarm optimization method with restricted search capabilities - Zhijian Liu; Yixiang Ma; Chenxing Hu; Haiyang Liu; Hongliang Zhang; Xin Li; Zhenhai Sun; Rui Rong; Zhijian Dong; Xiang Zhao; Guangpeng Yao (Sustainable Cities and Society, 2026)

Enhancing runoff simulation in data-scarce mountainous regions: a coupled SWAT and transferable transformer approach - Yi He; Rui Yan; Yanhong Tang; Jinyu Zhang; Hui Qian; Dejing Chen; Lei Zhu; Xin Cao (Journal of Hydrology, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Gallic acid-modified starch conjugates inhibit harmful aldehydes in fried battered fish: Based on structural characterization and antioxidant activity - Ying Li; Hao Zhang; Jiamu Kang; Meng Yang; Hanyu Liu; Wuyun Chen; Tingting Zhang; Deming Quan; Rui Zhang; Yuan Xia; Xin Du; Xiufang Xia (Food Research International, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Co-fermentation with autochthonous Levilactobacillus brevis and Lactiplantibacillus plantarum modulates metabolome and volatile profiles to improve the quality and safety of fermented chopped chili - Wenkai Jiang; Qian Yang; Luyao Xiao; Xia Fan; Menghan Zhong; Mahsa Ghahvechi Chaeipeima; Kai Ma; Changliang Zhang; Xin Rui; Wei Li (Food Research International, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Metabolomic changes following PMSG-induced estrus synchronization in Qianbei Ma goats - Feng-Xin Qiao; Yong-Hong Ju; Xiao-Dong Wang; Peng-Cheng An; Quan Ji; Rui-Yang Li; Ting-Ji Zeng; Qing Liu; Dai-Yue Zhang; Zu-Han Feng; Mao-Sheng Cao; Xiang Chen (Animal Reproduction Science, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Green preparation of graphene oxide-incorporated monoliths for pH-controlled protein enrichment and clinical biomarker detection - Xue Zhang; Fenghua Xu; Rui Wu; Huiying Zhang; Yufei Shi; Zhaosheng Liu; Xin Dong (Analytica Chimica Acta, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Integrated metabolomics and transcriptomics analyses provide insights into flavor and color regulation during tomato postharvest ripening - Xian-Kang Xiao; Wei-Xin Liu; Xiao Lu; Cai-Rui Chen; Xin-Yi Zhang; Xiao-Jun Pu; Feng Wang (Postharvest Biology and Technology, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Immobilized Pseudomonas sp. DNB-S1 on modified biochar enables synergistic DBP remediation and soil health enhancement - Rui Guan; Lei Wang; Jian Guan; Jianan Liu; Ying Zhang; Xiaochen Jia; Yarui Xin (Journal of Environmental Chemical Engineering, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Improved corrosion resistance of amorphous-containing dual-structured micro-arc oxidation coatings on (Zr0.5Ti0.35Nb0.15)90Al10 high-entropy alloy - Luqi Chai; Xuehui Yan; Yubo Ma; Lijiao Wang; Xin Li; Chungang Guo; Chi Xu; Jiancheng Du; Xiaoyue Jin; Wenbin Xue; Menglu Zhang; Rui Zuo (Chemical Engineering Journal, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

A deep learning multi-branch network method for landslide susceptibility mapping in the Sichuan-Tibet transportation corridor - Jichao Lv; Ruikai Hong; Xin Bao; Renzhe Wu; Xu He; Guoxiang Liu; Rui Zhang (Bulletin of Engineering Geology and the Environment, 2026)

Long-term reclamation enhances soil organic carbon accumulation via mitigating salinity and alkalinity in coastal saline soils - Wei Zhu; Shiguo Gu; Xin Zhang; Xuan Yu; Shuanghuang Yu; Xiangping Wang; Rui Jiang; Xiangtian Meng; Rongjiang Yao (Agriculture, Ecosystems & Environment, 2026)

Polysaccharide-mediated aging-modulatory effects of Labisia Pumila extracts on the physiological changes in C. elegans and D. melanogaster - Yinan Wang; Ahequeli Gemingnuer; Xuemei Zhang; Rui Yin; Xin Meng (Biogerontology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Editor's note to “Source identification and component characterization of dissolved organic matter in an acid mine drainage reservoir” [Sci. Total Environ. 739 (2020), 139732] - Jin Wang; Siyu Zhang; Chen He; Xin Pan; Yunyun Li; Rui Shao; Quan Shi; Zhengbo Yue (Science of The Total Environment, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Urbanization exacerbates riverine greenhouse gas (CO2, CH4, N2O) emissions on the Qinghai-Tibet Plateau - Yuwei Huang; Bangguo Wang; Shengying Ye; Queping Yang; Rui Xu; Jian Ma; Qinping Song; Philip K. Hopke; Yuejun He; Xin Zhang; Lijing Wang; Yuanxun Zhang (Journal of Environmental Management, 2026)

Continuous leachate irrigation as an ammonia source enhancing methane oxidation in landfill biocover soils - Ruo He; Rui Zhou; Lei Qian; Likun Xu; Xue Tong; Xin Zhang (Journal of Environmental Management, 2026)

New insights into late Quaternary dust activity and its drivers on the Tibetan Plateau from loess records - Li Liu; Shengli Yang; Yuanlong Luo; Pushuang Li; Xiuyun Yang; Xin Wang; Jingzhao Zhang; Weiming Liu; Rui Li; Xiaomin Fang (Global and Planetary Change, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Novel approach to binary protein construction via pulsed electric field-induced unfolding: Comprehensive enhancement of chickpea protein properties - Yongxin Teng; Xindong Xu; Boru Chen; Rui Wang; Ting Zhang; Xiangwei Zhu; Yonghui Li; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2026)

Enhancing rice yield and nitrogen use efficiency through OsRAV1 expression and crop management - Yingbo Gao; Haiyan Chao; Xinyi Zhao; Xin Liu; Chang Liu; Guanda Hu; Xueqin Chen; Guowei Wang; Dunliang Wang; Rui Li; Juan Zhou; Xiaoxiang Zhang; et al. (Field Crops Research, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Rewiring (p)ppGpp metabolism for high-yield anaerobic methanol and CO2 conversion in Butyribacterium methylotrophicum - Yuanke Guo; Feiyi Zhuang; Rui Zhang; Ruirui Qin; Jiao Feng; Kequan Chen; Xin Wang (Chemical Engineering Journal, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

Comprehensive observations of carbonyls in the Northern slope of the Tianshan Mountains: Characteristics, reactivity and sources - Kexin Wang; Minghao Dong; Hanran Liu; Xin Zhang; Yunfeng Li; Yafei Wang; Rui Gao; Jingjing Zhang; Yurong Li; Yu Chen; Zhaojiang Li (Air Quality, Atmosphere & Health, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

Machine learning-enhanced electrochemical sensing platform for simultaneous detection of multiple antibiotics in food samples - Ting Zhang; Yuan Sun; Xin Zhang; Wenyu Cui; Rui Liu (Food Chemistry, 2026)

NCOA4-mediated ferritinophagy regulates AgNP-induced ferroptosis in lung cells - Rui Zhang; Haitao Yang; Menghao Guo; Shuyan Niu; Yu Ma; Xin Shen; Liqing Wu; Chenyu Liu; Mengjing Cui; Tianshu Wu; Yuying Xue (Food and Chemical Toxicology, 2026)

Quantifying the impact of vegetation greenness change on surface urban heat islands across 133 major cities of China - Rui Yao; Zhihao Zhang; Wenjie Li; Hao Li; Shiya Zhu; Hongji Zhu; Chuan Wang; Dewei Luo; Ying Yang; Junli Li; Weitao Han; Xin Huang (Environmental Research, 2026)

Chemical characteristics and source apportionment of free amino acids in the Qinling forest atmosphere of central China - Xin Zhang; Rui Wang; Jianjun Li; Shuyan Xing; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Atmospheric Environment, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Heavy Metal Pollution Characteristics and Health Risk Assessment of Water Environment in Metal Mining Areas of the Han River Basin, Shaanxi Province - Longhao Huang; Yanmei Yang; Peng Zhang; Rui Meng; Xin Zhou; Qiang Zhou; Liansheng He; Zhihao Ye (Bulletin of Environmental Contamination and Toxicology, 2026)

Long-term removal of root carbon inputs has a great negative impact on grassland soil bacterial diversity, network stability and carbon and nitrogen cycling function - Rongrong Wu; Jilin Zhang; Haiyan Zhang; Xiao Zhang; Biao Dong; Yu Shi; Xin Jing; Rui Xiao; Cancan Zhao (Applied Soil Ecology, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Corrigendum to “An oxygen-independent therapeutic nanosystem for fighting against hypoxic and antioxidant microenvironment of tumor” [Journal of Photochemistry and Photobiology B: Biology 268 (2025) 113184] - Zixuan Wang; Shuwei Nie; Manru Wang; Huina Niu; Liqi Wei; Zhiqi Yang; Xin Liu; Yining Chen; Yunan Yang; Chunjiang Li; Qin Zhang; Lina Feng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Developing a radio frequency disinfestation technology for red jujubes with BaTiO3 as a filling material: Pest mortality, energy efficiency, and product quality - Xin Ye; Junjie Zheng; Jinsong Zhang; Longlong Jiang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Closed-loop biorefining of Moringa oleifera branches: unlocking nutraceutical polyphenols and fermentable sugars via NADES-mediated Cascade processing - Rui Zhang; Xin Zhou; Fuyu Yang; Yong Xu (Food Chemistry, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Quantifying drivers of wind drift and evaporation losses in sprinkler irrigation: A global meta-analysis - Rui Zhang; Xin Qiao; Delan Zhu; Pute Wu; Xiaomin Zhang (European Journal of Agronomy, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Inhibitory effects of various lignocellulose pretreatment byproducts on xylonic acid biosynthesis by Gluconobacter oxydans - Fan Li; Shuiping Ouyang; Rui Zhang; Xia Hua; Yong Xu; Xin Zhou (Bioresource Technology, 2026)

Interactions between cyanobacteria and emerging contaminants in aqueous environments - Yichen Yang; Xiaohan Zhang; Lingshen Tan; Rui Xin; Yongzheng Ma; Zhiguang Niu (Aquatic Toxicology, 2026)

Soluble TREM1 Contributes to Aging-Related Neurodegeneration via ROBO2/ERK Pathway - Jing-Wen Qi; Xin-Yu He; Yu-Cheng Gu; Zi-Jian Luo; Rui Duan; Ying-Dong Zhang; Yi Xie; Teng Jiang (Molecular Neurobiology, 2026)

Mechanisms of Action of FUNDC1 in Cerebral Ischemia-Reperfusion Injury - Xin-Yi Zou; Luo-Yang Cai; Jin Zhang; Ying Yuan; Jie Song; Zhao-Duan Hu; Rui Peng; Xiao-Feng Ruan; Xiao-Ming Zhang (Molecular Neurobiology, 2026)

Xinshuaining preparation ameliorates doxorubicin-induced cardiac injury in heart failure rats by regulating gut microbiota - Qian Nie; Jue Zhao; Sattar Haseeb; Siwei Deng; Xin Zhang; Rui Wang; Xu Luo; Wen Xie (Drug Delivery and Translational Research, 2026)

Novel interface-enhanced bimetallic nanozyme-mediated magnetic integrated nanoplatform for integrated prevention and control of pathogenic bacteria - Xiaoyu Yu; Xin Zhang; Yuwei Ren; Rui Jiao; Hui Li; Mengyu Li; Weichao Wu; Na Ling; Danfeng Zhang; Jianghua Cheng; Yingwang Ye (Analytica Chimica Acta, 2026)

A novel dual-polarization SAR vegetation index for crop phenology detection - Xin Bao; Rui Zhang; Xu He; Age Shama; Gaofei Yin; Jie Chen; Hongsheng Zhang; Guoxiang Liu; Xianjian Shi (Computers and Electronics in Agriculture, 2025)

Two meroterpenoids from the root bark of Eucalyptus robusta - Yi-Yang Chen; Yong-Xin Wei; Rui-Zhen Chen; Kun-Feng Zhang; Ling-Yi Kong; Ming-Hua Yang (Phytochemistry Letters, 2025)

Small-sized fixed domain monitoring underwater profiler: A multi-factor comparative analysis - Yang Zhang; Xin Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Rui Zhou; Jiayu Hou; Gul Muhammad (Ocean Engineering, 2025)

Screening and characterization of marine cyanobacteria for dairy farm wastewater treatment: Nodosilinea sp. E11 as a promising candidate for phycoremediation - Meiqi Zhang; Rui Xin; Yu Wang; Keqiang Zhang (Journal of Cleaner Production, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Field observations and computational insights into VOC emissions and associated health risks from semi-coking industries in Shaanxi province - Wenxuan Sun; Rui Gao; Xin Zhang; Ledong Zhu; Manfei Yin; Kexin Wang; Wenxing Wang; Qiao Wang (Journal of Environmental Sciences, 2025)

Xylo-oligosaccharide utilization by Weissella kandleri YT103: Transcriptomic analysis and intestinal barrier protection - Xin-rui Zhang; Shuang-shuang Cui; Long-fen Yin; Gui-zhen Gong; Jian-xia Yang; Yang Chen; Yuan-ting Zhu (Food Research International, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Molecular characteristics of brown carbon aerosols over a forest atmosphere in the Qinling region of central China - Xin Zhang; Shuyan Xing; Jianjun Li; Rui Wang; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Environmental Pollution, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Critical review of integrated CO2 capture and conversion via calcium-looping dry reforming of methane - Rui Fang; Tuo Zhou; Haowen Wu; Tong Wang; Yinqiang Song; Man Zhang; Xin Meng; Yupeng Feng; Hairui Yang (Chemical Engineering Journal, 2025)

Hdac11 inhibits apoptosis in zebrafish cells under cold stress via downregulating pdcd6 through its downstream enhancer - Mingzhi Ma; Juntao Luo; Xin Li; Rui Deng; Hui Jiang; Bingshe Han; Junfang Zhang (Molecular Biology Reports, 2025)

The comprehensive review of eucalyptol: synthesis, metabolism, and therapeutic applications in disease treatment - Bin Yao; Bin He; Jiahua Peng; Xin Song; Rui Zhao; Yu Sun; Yanfang Zhang (Molecular Biology Reports, 2025)

Effect of Manure Application on Few Soil Properties and Crop Yield Under Greenhouse Cultivation-a Comprehensive Analysis - You Wu; Jiale Zhang; Wei Si; Rui Liu; Zhenxin Qiu; Jianhua Yang; Renlei Luo; Xin Lei; Weiqi Wang; Musa Ma; Xinhao Yang; Cheng Yang (Journal of Soil Science and Plant Nutrition, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Enhancing performance of SSVEP-based visual acuity via exploiting subject-specific information - Xiaowei Zheng; Boyu Wen; Xin Yan; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2025)

Wheat straw incorporation and nitrogen fertilization increase antibiotic resistance gene abundance and dissemination potential in agricultural soil - Feng-Hua Wang; Rui-Ao Ma; Zi-Teng Liu; Xin-Di Zhao; Ruibo Sun; Wenxu Dong; Yuming Zhang; Min Qiao; Si-Yu Zhang (Soil Ecology Letters, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

Evaluation of efficacy of intensity measures for fast and reliable seismic fragility analysis of bridge columns - Jian-Cheng Dai; Dong-Sheng Wang; Xiao-Yu Chen; Wei-Jian Tang; Rui Zhang; Ying-Xin Hui (Soil Dynamics and Earthquake Engineering, 2025)

Impact of large-scale climate indices on total nitrogen concentrations in drinking water sources cannot be overlooked - Ning Li; Jingfeng Xiao; Zheng Zhang; Rui Bai; Jiayi Yong; Ziyu Ning; Miao Chen; Yaxiong Chen; Shuli Xin; Shengwu Xiong (Journal of Hydrology, 2025)

Electrochemical dimerization of furfural and 5-hydroxymethylfurfural into aviation fuel precursors: Optimization and mechanistic insights - Jiahui Chen; Xian Pan; Xinchi Zhang; Xin Zhou; Shiliang Wu; Youn-Sang Bae; Ismagil Shakirovich Khusnutdinov; Feng Gong; Tao Li; Huiyan Zhang; Rui Xiao (Journal of Cleaner Production, 2025)

The potential of anthraquinone-2-sulfonate (AQS) for “shell breaking” of iron-coated denitrification granular sludge - Xin-Rui Zhang; Zhi-Han Xi; Zi-Jun Yan; Xin-Tao Liu; Ying Wang; Run-Mei Li; Zi-Yue Li; Ke-Yu Wu; Ren-Cun Jin; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Management, 2025)

Higher ammonia oxidizing activity of comammox cooperates with ammonia-oxidizing bacteria to release N2O in river ecological restoration areas - Yuantao Wang; Shenghua Zhang; Rui Jia; Xin He; Ang Li; Dongdan Yuan (Journal of Environmental Management, 2025)

Qualitative and quantitative detection of Zn2+ in food: design, synthesis and characterization of a near-infrared probe with large Stokes shift - Shizhen Wang; Xin Wang; Wenhui Xue; Yi Huo; Mengyu Chen; Cuibing Bai; Qixiang Song; Chenxu Liu; Lin Zhang; Changqing Qu; Hui Miao; Rui Qiao (Food Chemistry, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

Dynamic response of ceramic-reinforced metallic corrugated sandwich structures under combined blast-fragment loading - Chang-ye Ni; Cong Luo; Lu-sheng Qiang; Xin-yi Bai; Jia-le Wu; Jian-hong Zhang; Rui Zhang (Engineering Structures, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Ni/Al2O3 catalysts for the selective hydrogenation of 1,3–butadiene to butene: From theoretical research to experimental proving - Linxia Cui; Mingyuan Zhang; Xin Chen; Yuanyao Xie; Yang Jiang; Rui Gao; Haigang Hao (Chemical Engineering Journal, 2025)

Cinnamaldehyde enhanced starch/chitosan composite films: A one-pot engineered solution for extended fruit shelf life - Qingbo Yao; Yan Chen; Zhizhi Zhang; Weijian Chen; Rui Wang; Langhong Wang; Yanyan Huang; Fengsong Liu; Xin-An Zeng (Carbohydrate Polymers, 2025)

Correction: Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Macrophage cytoskeletal and immune responses to photoaged and gastrointestinal-transformed polylactic acid micro/nanoplastics with protein corona - Xuri Wu; Feng Tan; Han Zhang; Liping Huang; Yan Wang; Xin He; Rui Cai; Shumin Li (Journal of Hazardous Materials, 2025)

The interactions, impacts, and removal strategies of microplastics (MPs) and antibiotic resistance genes (ARGs) in aquatic environments, particularly in wastewater treatment plants (WWTPs) - Ying Wang; Xin-Rui Zhang; Min-Min Qiang; Zheng Huang; Xin-Tao Liu; Run-Mei Li; Zi-Yue Li; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Light-confining resonant metamaterial integrated with silicon-doped quantum dots for liquid-phase biomolecular detection - Rui Zhang; Jie Huang; Lanju Liang; Zhuyu Ding; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun (Chemical Engineering Journal, 2025)

Self-activated antibacterial mask through respiratory induced deformation and temperature variation - Liqi Wei; Li Liu; Qin Zhang; Wenye Xie; Zhiqi Yang; Xin Liu; Yunan Yang; Yining Chen; Yiping Ren; Tianshu Zou; Biao Zhang; Hongxia Ma; et al. (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Rockburst Severity Prediction Under Few-Shot Conditions Using Feature Fusion Learning - Xin Cai; Liye Chen; Yichao Rui; Ruishan Cheng; Zilong Zhou; Jixiong Zhang; Hang Yuan; Yunmin Wang (Natural Resources Research, 2025)
Accurate and efficient prediction of rockburst severity is crucial for the safe construction of deep rock engineering, but only a limited number of recorded rockburst data cannot enable the reliable prediction. This paper presents an innovative method for predicting rockburst severity, termed Feature Fusion Learning (FFL). It combines feature fusion with machine learning models and category voting techniques, enabling square-level amplification of sample data to address the challenge of few-shot in predicting rockburst severity. The performance of this method is evaluated against two typical data augmentation techniques (i.e., noise injection and synthetic minority over-sampling technique) combined with three machine learning models (i.e., extreme gradient boosting, light gradient boosting machine, and random forest). The results indicate that the FFL method exhibits superior performance across all metrics compared to the other models. In addition, feature importance assessments and a comparative study on the effect of amount of prior data on the prediction performance of the FFL method are conducted. The results reveal that the FFL method effectively enriches the feature dimensions while preserving the information and properties of the original feature variables. Moreover, the FFL method shows high robustness when applied to datasets with varying sample sizes.

Nurturing soil health: the interconnected roles of biochar and arbuscular mycorrhizal fungi - Zitian Pu; Rui Hou; Zhihong Xie; Ruifang Zhang; Xuguang Li; Xin-Xin Wang (Journal of Soils and Sediments, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Investigating the mechanism of Fuling-Banxia-Dafupi in the treatment of diabetic kidney disease using network pharmacology and molecular docking - Qi Wang; Yiran Pang; Han Yang; Xin Zhang; Weichen Nie; Jiahui Zhou; Rui Chen (Natural Product Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Developing a novel radio frequency dehydration process based on heating uniformity, drying characteristics, and product quality of white tea - Xin Ye; Jinsong Zhang; Junjie Zheng; Mengge Li; Dongsheng Hu; Liumin Fan; Rui Li; Shaojin Wang (Journal of Food Engineering, 2025)

Enhancement of soil DOC and electron transport by biochar strengthens Cd immobilization via iron oxides transformations in waterlogged soils - Xin Chen; Tianren Si; Senhan Wang; Rui Yuan; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Modulating band structure of MoO3 via W-doped for enhanced photo-induced charge transfer and SERS detection - Hongwen Cao; Yunpeng Cao; Jia He; Xin Xie; Zhijun Wang; Sen Sun; Rui Zhong; Lei Sun; Yihan Wang; Kun Zhang (Chemical Engineering Journal, 2025)

Multilevel surface enhancement of primary and secondary particles in cobalt-free high-nickel cathode material through Mo and W staged doping - Dandan Sun; Jiyuan Jian; Xin Zhang; Shuang Lin; Yixuan Qiao; Tao Wu; Xianhui Zhao; Rui Xiao; Ziwei Liu; Hua Huo; Pengjian Zuo; Yulin Ma; et al. (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Assessing the nicotinic acetylcholine receptor-mediated enantioselective neurotoxicity of a neonicotinoid-like pollutant, chiral sulfoxaflor: Insight from the two asymmetric centers - Zhi-Cong He; Tao Zhang; Xin-Fang Lu; Rui Li; Wei Peng; Qiong Mei; Qi-Zhao Wang; Fei Ding (Journal of Hazardous Materials, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Vanadium dioxide - Perovskite tandem smart windows achieve full-spectrum modulation via plasmonic Fabry-Pérot engineering - Qiuyi Shi; Bowen Li; Yuwei Du; Sai Liu; Rui Zhang; Cancheng Jiang; Xin Li; Muhammad Fahim; Irum Firdous; Johnny C.Y. Ho; Chi Yan Tso (Chemical Engineering Journal, 2025)

Assessment of Thermal Vulnerability and Analysis of Influencing Factors in Urban Functional Areas of Foshan City, China - Xinyue Wang; Jun Yang; Rui Zhang; Jiaxing Xin; Wenbo Yu; Jiayi Ren; Xiangming Xiao (Chinese Geographical Science, 2025)

Elucidating the anti-aging bioactive compounds and mechanisms of Jingfang Granules formula based on network pharmacology and Caenorhabditis elegans - Rui Zhao; Taili Zhao; Tingting Shi; Chuanjiao Feng; Honghua Li; Ying Xu; Qingqing Zhang; Xin Yin; Jingchun Yao; Guimin Zhang; Xuekui Xia (Biogerontology, 2025)

Advances in anammox process for municipal wastewater treatment plants: A review focusing on applied study and full-scale implementation cases - Xin Yin; Wenqi Li; Meng Zhang; Rui Du; Chongjun Chen (Critical Reviews in Environmental Science and Technology, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

An oxygen-independent therapeutic nanosystem for fighting against hypoxic and antioxidant microenvironment of tumor - Zixuan Wang; Shuwei Nie; Manru Wang; Huina Niu; Liqi Wei; Zhiqi Yang; Xin Liu; Yining Chen; Yunan Yang; Chunjiang Li; Qin Zhang; Lina Feng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Potentially toxic elements in sediments of China's Shihe River: Urban-agricultural impact assessment and source apportionment - Kai Zhang; Ge Ma; Zheng Chen; Jilu Wang; Xiaomeng Lou; Yinan Yang; Jiaojiao Feng; Fengxia Yang; Kuangjia Li; Chenxuan Shang; Rui Xin; Xiangmin Zhang (Journal of Contaminant Hydrology, 2025)

Responses of an invasive plant Alternanthera philoxeroides to cadmium, nutrient availability and water temperature - Zi-Yang Xie; Zhi-Hang Liu; Xin-Yue Gu; Yuan-Yuan Qin; Yu-Ting Du; Jin Yan; Rui Zhang; Chao Si (Aquatic Botany, 2025)

Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

Calcium phytate cross-linked polysaccharide hydrogels for selective removal of U(VI) from tailings wastewater - Lan Lei; Rui Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Xin Liu; Tie-Ying Shi; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Water Research, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Ginsenoside F2 inhibits MLCK to induce synthetic lethality in MYC-driven triple-negative breast cancer and pancreatic cancer - Rui Wu; Dong Lu; Xin Luan; Weidong Zhang; Zhe Sun (Phytochemistry Letters, 2025)

Research on the dynamical behavior of air-dropped underwater profiler and virtual mooring strategy for variable pitch angle - Dingze Wu; Rui Zhou; Qingchao Xia; Puzhe Zhou; Xin Zhang; Zhilan Jin; Yang Zhang; Canjun Yang (Ocean Engineering, 2025)

Validation of industrial radio frequency treatment protocols to control Lasioderma serricorne in tobacco leaves - Jinsong Zhang; Xin Ye; Zijun Mo; Gaoji Yang; Rui Li; Shaojin Wang (Journal of Stored Products Research, 2025)

Amelioration of Kluyveromyces marxianus GY-8 on high-fat diet-induced obesity and gut microbiota dysbiosis - Nanyu Tang; Xiaogan Zhao; Tao Lin; Yihan Lin; Chang Xu; Kai Ma; Changliang Zhang; Feng Ji; Ghahvechi Chaeipeima Mahsa; Luyao Xiao; Xin Rui; Wei Li (Food Bioscience, 2025)

In vitro experiments and computer simulation techniques on the identification, screening and inhibition mechanism of xanthine oxidase (XO) inhibitory peptides from Esox lucius bone - Rui Geng; Yabo Wei; Yi Wang; Xin Guo; Xiaorong Deng; Lianfu Zhang; Jian Zhang (Food Bioscience, 2025)

Corrigendum to ‘Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions’ [Desalination 603 (15 May 2025) 118606] - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

Highly sensitive and wash-free human serum albumin detection based on filtration-to-enhancement compound microsphere system - Chen Yang; Xin Zhang; Minjing Mo; Guoqing He; Menglu Gao; Tao Jiang; Yihan Ma; Xiaotong Si; Rui You; Fubing Wang; Yi Yang (Chemical Engineering Journal, 2025)

Bimetallic organic framework-derived multifunctional signal marker-driven ultra-magnetic nanoplatform for sensitive detection and efficient sterilization of methicillin-resistant Staphylococcus aureus - Xin Zhang; Xiaoyu Yu; Yuwei Ren; Rui Jiao; Hui Li; Xiyan Zhang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; Yingwang Ye (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The Influence of Vickers Hardness and Brittleness on Particle Size Distribution During Ball Milling: A Multifractal Approach - Sheng Zhang; Yichao Rui; Zilong Zhou; Xin Cai; Hongzhi Cui (Rock Mechanics and Rock Engineering, 2025)

A comprehensive review of m6 A methylation in coronary heart disease - Mei-Ning Diao; Yi-Jv Lv; Hui Xin; Yin-Feng Zhang; Rui Zhang (Journal of Molecular Medicine, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Modelling soil water and its uniformity under linear-move sprinkler irrigation - Rui Zhang; Xin Qiao; Delan Zhu; Pute Wu; Xiaomin Zhang (Biosystems Engineering, 2025)

Thermal death kinetics of pests in tobacco leaves as influenced by heating rates and life stages - Jinsong Zhang; Xin Ye; Zijun Mo; Hongwei Wang; Xican Gu; Jiaqin Xi; Rui Li; Shaojin Wang (Journal of Stored Products Research, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Time-series InSAR landslide three-dimensional deformation prediction method considering meteorological time-delay effects - Jichao Lv; Rui Zhang; Xin Bao; Renzhe Wu; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2025)

Design of polypyrrole layer enhanced MIL-88B(Fe) composite electrode material for electrosorption separation of copper ions - Lujie Nie; Yanna Ren; Lei Wang; Yingying Wang; Jiajun An; Jiajin Hao; Jiaqi Wang; Chen Zhao; Xin Zhang; Yongtao Lv; Miaolu He; Hongyun Nie; et al. (Desalination, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Recent advances and future prospects of wearable sensors based on nanomaterial sensing mechanisms for biosafety monitoring - Xiaoyu Yu; Hui Li; Junwen Wang; Xin Zhang; Rui Jiao; Yuwei Ren; Danfeng Zhang; Na Ling; Yingwang Ye (Chemical Engineering Journal, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Synthesis, characterization, and catalytic performance of a novel and efficient iron-based catalyst NaFeS2 for direct coal liquefaction - Rui Zhang; Bowen Tang; Haiyun Liu; Xin Zheng; Zhixian Bao; Lijun Jin; Jianli Wang; Haoquan Hu (Fuel, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Landslide detection based on pixel-level contrastive learning for semi-supervised semantic segmentation in wide areas - Jichao Lv; Rui Zhang; Renzhe Wu; Xin Bao; Guoxiang Liu (Landslides, 2025)

Intelligent identification and semantic segmentation of deep rock fracture based on deep ensemble learning and transfer learning - Rui Li; Qingsong Zhang; Shaoxuan Guo; Guangxuan Zhu; Hongzhao Li; Xin Chen; Junlong Yan (Tunnelling and Underground Space Technology, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Multiomics unraveled that gibberellin signaling underlies adaptation of rice to ciprofloxacin stress: Calling for concerns on the adverse effects of pharmaceutical residues in water during agricultural irrigations - Xin Qi; Rui Zhao; Xiaona Zhang; Shaoguo Ru; Jiu-Qiang Xiong (Journal of Hazardous Materials, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Structural evolution of Ni-Ce bimetallic alloy on Al2O3 support in methane dry reforming: Achieving sustainability and high-efficiency reaction through cerium modulation strategy - Xu Ma; Wei-Wei Yang; Jia-Rui Zhang; Xin-Yuan Tang (Fuel, 2025)

Insight of oil-soluble Fe-based catalyst for direct liquefaction of Shangwan coal - Zhi Li; Yuxin Wen; Rui Zhang; Mei Zhong; Haiyun Liu; Xin Zheng; Haoquan Hu; Lijun Jin (Fuel, 2025)

Oral delivery of extracellular vesicles from goat milk alters the microbiota, enhances the immune response, and strengthens the barrier function in the intestine of mice - Ziwei Wang; Xinlong Zhang; Rui Chen; Hongxu Zhu; Xiaolai Xie; Hangshu Xin; Peixin Jiao (Food Bioscience, 2025)

Highly selective ppb-level Cl2 sensor at room temperature based on ZIF-8 coated MIL-68(In)-derived hexagonal tubes - Sumin Wang; Rui Gao; Ming Zheng; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Xin Zhou; Lihua Huo (Chemical Engineering Journal, 2025)

Enhancing the co-utilization of methanol and CO2 into 1-butanol by equipping synergistic reductive glycine pathway in Butyribacterium methylotrophicum - Jing Wang; Shengji Li; Chenxi Ma; Rui Zhang; Jialun Qin; Kequan Chen; Xin Wang (Bioresource Technology, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

YOLO-RCS: A method for detecting phenological period of 'Yuluxiang' pear in unstructured environment - Rui Ren; Shujuan Zhang; Haixia Sun; Ning Wang; Sheng Yang; Huamin Zhao; Mingming Xin (Computers and Electronics in Agriculture, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

A TiO2/ZnO (nanoparticle/quantum dot) heterojunction with strong interfacial coupling for ultrasensitive SERS sensing of antibiotic residues in environment (water and soil) and their efficient degradation - Yimin Tang; Xuewei Zhang; Rui Wang; Huizhu Zhang; Libin Yang; Xin Jiang; Bing Zhao (Journal of Environmental Chemical Engineering, 2025)

Diselenide bond-stapled β-hairpin peptide-loaded hydrogel system for boosting oncolytic immunotherapy - Shengxin Lu; Xiaokun Zhang; Jiayi Lin; Rui Liang; Yiting Gong; Long Gao; Aoyu Cheng; Xinchen Lu; Hongzhuan Chen; Ye Wu; Weidong Zhang; Xin Luan (Chemical Engineering Journal, 2025)

Revealing the combined effect of hydroxylamine and hydrazine on nitrogen removal performance of completely autotrophic nitrogen removal over nitrite (CANON) process - Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The Effect of Disc Degeneration on the Biomechanical Response of the Lumbar Spine under Vibration Loading Condition - Bin Zhang; Tian-Cheng Li; Xin Wang; Rui Zhu; Cheng-Fei Du; Yuan Xie (Journal of Medical and Biological Engineering, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Nitrogen@Carbon Quantum Dots for Fluorescence Detection of L-alanine, L-methionine and L-cysteine - Xin Chen; Qing-wan Wang; Tong-ling Zhan; Yue Sun; Xiao-rui Zhang; Kun Liu; Xiao-wu Liu (Journal of Fluorescence, 2025)

Grevillosides R-S: glucosides of 5-alkylresorcinol derivatives from roots of Ardisia crispa (Thunb.) A. DC - Xing-xiang Long; Shuang Zhang; Li-juan Xiang; Rui-hang Hu; Ting-ting Feng; Ying Zhou; Xin Yin (Natural Product Research, 2025)

Corrigendum to “Vimentin rearrangement by phosphorylation is beneficial for porcine reproductive and respiratory syndrome virus replication in vitro” [Vet. Microbiol. 259 (2021) 109133] - Xin-xian Zheng; Rui Li; Songlin Qiao; Xin-xin Chen; Longxiang Zhang; Qingxia Lu; Guangxu Xing; En-min Zhou; Gaiping Zhang (Veterinary Microbiology, 2025)

Microwave replacing traditional concentrating process to promote the synthesis of mumefural in Prunus mume extract - Teng Long Miao; Shan Qin; Xiao Hong Chen; Long Yun Chen; Yan Qing Han; Yan Li Yuan; Xin Rui; Wei Li; Qiu Qin Zhang (Food Research International, 2025)

Platinum-based fluorescent nanozyme-driven “loong frolic pearls” multifunctional nanoplatform for tri-mode ultrasensitive detection and synergistic sterilization of Burkholderia gladioli - Rui Jiao; Yuwei Ren; Xiyan Zhang; Hui Li; Ying Zhan; Xin Zhang; Xiaoyu Yu; Na Ling; Yingwang Ye (Food Chemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Efficient resource recovery from food waste digestate via hydrothermal treatment and its application as organic fertilizer - Hong Chen; Jun Sheng; Qinhui Ye; Jun Li; Xin Yu; Hanyue Wu; Rui Zhang; Shiyi Zhao; Xiaoming Zou; Xiang Li; Gang Xue; Baoling Yuan (Bioresource Technology, 2025)

A systemic review of yak milk and its products on the Qinghai-Tibet Plateau: Unique products, chemical composition, biological activities, and microbial composition - Zhiqiang Liang; Xiaoqian Chen; Xinyu Wang; Xiaoxi Qi; Lina Zhang; Yu Xin; Zhenyu Yang; Rui Fan; Yang Li; Libo Liu; Chun Li (Trends in Food Science & Technology, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Transcription combined metabolic analysis reveals the mechanism of potassium phosphate enhances resistance to walnut anthracnose (Colletotrichum gloeosporioides) - Guifang Wang; Yuantao Yao; Haifeng Xu; Kun Xiang; Meiyong Zhang; Junpei Zhang; Rui Zhang; Xin Chen (Postharvest Biology and Technology, 2024)

Palynological assemblages from Hongguleleng Formation of Western Junggar, Northwest China and their correlation with conodont zonation - Zhen Shen; Philippe Steemans; Zélia Pereira; Rui-Wen Zong; Xin-Song Zhang; Kun-Yuan Ma; Yi-Ming Gong (Palaeoworld, 2024)

Spatio-temporal dynamics and recovery of commuting activities via bike-sharing around COVID-19: A case study of New York - Mengjie Gong; Rui Xin; Jian Yang; Jiaoe Wang; Tingting Li; Yujuan Zhang (Journal of Transport Geography, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

Effects of relative humidity on atmospheric organosulfur species derived from photooxidation and nocturnal chemistry in a forest environment - Lijuan Li; Jianjun Li; Xin Zhang; Yue Lin; Rui Wang; Junji Cao; Yuemei Han (Environmental Pollution, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

The Influence of pH on Sulfamethoxazole in Soil Systems: Migration and Degradation - Haifang Wang; Xin Li; Zhumei Sun; Xia Cao; Junli Zhang; Qihua Chen; Rui Ma (Water, Air, & Soil Pollution, 2024)

COL6A3 enhances the osteogenic differentiation potential of BMSCs by promoting mitophagy in the osteoporotic microenvironment - Kun Wang; Xin Peng; Rui Zhang; Xiaotao Wu; Lu Mao (Molecular Biology Reports, 2024)

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Iron-modified biochars and their aging reduce soil cadmium mobility and inhibit rice cadmium uptake by promoting soil iron redox cycling - Tianren Si; Xin Chen; Rui Yuan; Siyu Pan; Yan Wang; Rongjun Bian; Xiaoyu Liu; Xuhui Zhang; Stephen Joseph; Lianqing Li; Genxing Pan (Journal of Environmental Management, 2024)

Mn vacancy engineering design of Fe/Mn based cathodes for breaking the spell between “sodium limiting” in air-stabilization and “sodium promoting” on kinetics - Rui Huang; Shaohua Luo; Qi Sun; Xin Yan; Haoran Zhang; Lixiong Qian; Xin Liu; Xingzhong Cao; Peng Zhang; Shengxue Yan (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Simulating droplet distribution characteristics in sprinkler irrigation using a modified ballistic model under multifactor coupling - Rui Zhang; Yichuan Liu; Delan Zhu; Pute Wu; Ke Xin; Xiaomin Zhang; Nazarov Khudayberdi; Changxin Liu (Computers and Electronics in Agriculture, 2024)

The presences of water in the generation of calc-alkaline I-type granitic magmas at continental arc: Insight from Neoproterozoic Ailaoshan magmatism at the southwestern margin of the Yangtze Block, South China - Bin Huang; Rui Li; Nimat Ullah Khattak; Xin-Yu Cai; Yang Zhang; Wei Wang (Precambrian Research, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

Dietary flavonoids: Role in preventing neurodegenerative diseases caused by brain aging by modulating the gut microbiota - Siyu Liu; Haochen Dai; Rui Wang; Xin Zhang (Food Bioscience, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

An efficient Au/ZnO catalyst for the photocatalytic conversion of methane to formaldehyde - Yan-Qun Chen; Lei-Xin Mao; Rui-Xin Zhang; Xin-Yu Zhang; Zhi-Hua Gao; Lei Liu; Wei Huang; Zhi-Jun Zuo (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

The association between the scarlet fever and meteorological factors, air pollutants and their interactions in children in northwest China - Donghua Li; Yanchen Liu; Wei Zhang; Tianshan Shi; Xiangkai Zhao; Xin Zhao; Hongmiao Zheng; Rui Li; Tingrong Wang; Xiaowei Ren (International Journal of Biometeorology, 2024)

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

Shoot and Root Traits are Associated with Varying Soil Phosphorus Supply in Chinese Cabbage - Hou Sai-sai; Pu Zi-tian; Zhang Rui-fang; Zhang Chi; Wang Hong; Wang Xin-xin; Zhao Jian-jun (Journal of Soil Science and Plant Nutrition, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Mechanisms for carbon stock driving and scenario modeling in typical mountainous watersheds of northeastern China - Jin Zhang; Wen-Guang Zhang; Xin-Yan Zhang; Yu-Hong Li; Ming-Ming Feng; Peng Qi; Yi-Qiang Huang; Rui Li; Ming Jiang; Yuan-Chun Zou; Yi Wu (Environmental Monitoring and Assessment, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

Correction to: Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Novel insights into the relationship between the functional groups and photoactivity of biochar-derived dissolved organic matter - Xin Zuo; Zhuozhi Ouyang; Jinmo Liao; Rui Ding; Weiwei Zhang; Chi Zhang; Xuetao Guo; Lingyan Zhu (Water Research, 2024)

Carbon dioxide radical anion mediated dehalogenation kinetics and mechanisms of halogenated alkanes - Xinran Zhang; Rui Zhang; Pengfei Ren; Jianhua Zhou; Weiguang Li; Xin Yang (Water Research, 2024)

In situ real-time pathway to study the polyethylene long-term degradation process by a marine fungus through confocal Raman quantitative imaging - Wanying He; Rui Liu; Fan Fei; Shichuan Xi; Zengfeng Du; Zhendong Luan; Chaomin Sun; Xin Zhang (Science of The Total Environment, 2024)

Graph deep learning recognition of port ship behavior patterns from a network approach - Rui Xin; Jiale Pan; Fanlin Yang; Xiongfeng Yan; Bo Ai; Qianran Zhang (Ocean Engineering, 2024)

Enhanced photocatalytic U(VI) reduction via double internal electric field in CoWO4/covalent organic frameworks p-n heterojunction - Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Xiao-Xing Wang; Xin Liu; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Exploring the spatial patterns of landslide susceptibility assessment using interpretable Shapley method: Mechanisms of landslide formation in the Sichuan-Tibet region - Jichao Lv; Rui Zhang; Age Shama; Ruikai Hong; Xu He; Renzhe Wu; Xin Bao; Guoxiang Liu (Journal of Environmental Management, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Gas chromatography-mass spectrometry and non-targeted metabolomics analysis reveals the flavor and nutritional metabolic differences of cow's milk fermented by Lactiplantibacillus plantarum with different phenotypic - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

In-situ controllable preparation of ZIF-8-wrapped ZnO heterojunction nanorods array for ppb-level Cl2 detection operated at near room temperature - Xiaoqian Meng; Rui Gao; Ming Zheng; Xin Zhou; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

SSVEP-based visual acuity threshold estimation: linear extrapolation to noise level baseline with various noise definition criteria - Xiaowei Zheng; Xin Wei; Guanghua Xu; Rui Zhang (Cognitive Neurodynamics, 2024)

Genome-based classification of the family Haloferacaceae and description of five novel species of Halobaculum - Shun Tan; Ling-Rui Zhu; Qing-Ke Zhang; Xin-Yue Dong; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Dual-Mode Square Root Cubature Kalman Filter for Miniaturized Underwater Profiler Dead Reckoning - Yang Zhang; Qingchao Xia; Canjun Yang; Ruiyin Song; Dingze Wu; Xin Zhang; Rui Zhou; Shuyang Ma (Journal of Marine Science and Engineering, 2024)
Miniaturized underwater profilers have the advantages of small size, low cost, and flexible deployment, which play together an important role in the persistent monitoring of a designated ocean area. Based on the demand for ocean observation, the system design, dynamic modeling, and dead reckoning algorithm of a miniaturized underwater profiler are carried out. The process of the persistent monitoring of designated area with a miniaturized underwater profiler is analyzed, and the overall structure of the miniaturized underwater profiler was designed. Additionally, the kinematic and dynamic model of the miniaturized underwater profiler is given based on the inertial and body coordinate systems. Then, according to the state equation and the observation equation of the miniaturized underwater profiler, a dual-mode square root cubature Kalman filter (DSRCKF) algorithm, combining standard SRCKF and adaptive SRCKF, is proposed for the dead reckoning of the miniaturized underwater profiler. Finally, a comprehensive comparison of EKF, UKF, CKF, SRCKF, and DSRCKF and the associated simulations and experiments are conducted to verify the performance of the underwater dead reckoning algorithm for the miniaturized underwater profiler. The results show that the DSRCKF algorithm has a certain role in the dead reckoning of the miniaturized underwater profiler, particularly in the z direction and attitude. In future, a real underwater dead reckoning test using miniaturized underwater profiler will be carried out.

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Response of GFRP suction bucket in clay during installation - Hai-lei Kou; Zhao-tun An; Yong-kang Wang; Hong-rui Zhang; Xi-xin Zhang (Ocean Engineering, 2024)

Effects of different cold chain logistics modes on the quality and bacterial community succession of fresh pork - Su Wang; Dequan Zhang; Qingfeng Yang; Xiangyuan Wen; Xin Li; Tongjing Yan; Rui Zhang; Wei Wang; Kumayl Hassan Akhtar; Caiyan Huang; Chengli Hou (Meat Science, 2024)

Detoxification and removal of heavy metal by an acid-tolerant microalgae, Graesiella sp. MA1 - Lu Zhang; Jin Wang; Rui Shao; Xin Chuai; Shaoping Wang; Zhengbo Yue (Journal of Water Process Engineering, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Hydrogen-donating behavior and hydrogen-shuttling mechanism of liquefaction solvents under Fe- and Ni-based catalysts - Haiyun Liu; Rui Zhang; Xin Zheng; Jing Xie; Bowen Tang; Zhi Li; Erguang Guo; Haoquan Hu; Lijun Jin (Fuel, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Fish skin mucosal surface becomes a barrier of antibiotic resistance genes under apramycin exposure - Wenpeng Li; Xiaohan Zhang; Xiaohan Hao; Rui Xin; Ying Zhang; Yongzheng Ma; Zhiguang Niu (Environmental Research, 2024)

Victoria amazonica-inspired sandwich-structure interfacial solar steam generator - Junjie Pan; Xin Zhang; Chenglong Zhang; Wenfeng Hu; Siyi Bi; Huiqi Shao; Nanliang Chen; Rui Yu; Jinhua Jiang; Guangwei Shao (Chemical Engineering Journal, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

The Association Between the Levels of Oxidative Stress Indicators (MDA, SOD, and GSH) in Seminal Plasma and the Risk of Idiopathic Oligo-asthenotera-tozoospermia: Does Cu or Se Level Alter the Association? - Tao Yin; Xinyu Yue; Qian Li; Xinyu Zhou; Rui Dong; Jiayi Chen; Runtao Zhang; Xin Wang; Shitao He; Tingting Jiang; Fangbiao Tao; Yunxia Cao; et al. (Biological Trace Element Research, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Degradation of quinolone antibiotics by freeze activated periodate: effect of the number of fluorine substituents and DFT calculations - Hao Lin; Yan Zhang; Yucan Liu; Xiuping Sun; Bin Ji; Rui Mei; Tongshuai Liu; Zhonglu Gao; Xin Wang (Journal of Environmental Chemical Engineering, 2024)

Highly sensitive detection of aflatoxin B1 byCRISPR/Cas12a-assisted single nanoparticle counting - Chengchao Zhang; Xin Zhao; Zili Huang; Ziyan Li; Jianyu Hu; Rui Liu; Yi Lv (Food Chemistry, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Potential in exosome-based targeted nano-drugs and delivery vehicles for posterior ocular disease treatment: from barriers to therapeutic application - Xingru Peng; Tingting Zhang; Rui Liu; Xin Jin (Molecular and Cellular Biochemistry, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

H5N1 high pathogenicity avian influenza virus in migratory birds exhibiting low pathogenicity in mallards increases its risk of transmission and spread in poultry - Qiuyan Mao; Zhixin Li; Yuecheng Li; Yaxin Zhang; Shuo Liu; Xin Yin; Cheng Peng; Rui Ma; Jinping Li; Guangyu Hou; Wenming Jiang; Hualei Liu (Veterinary Microbiology, 2024)

Records of deep-sea turbidity current activity in the Bengal Fan since the Last Glacial Maximum - Jingrui Li; Xin Shan; Xuefa Shi; Shengfa Liu; Shuqing Qiao; Hui Zhang; Kaikai Wu; Xiaoming Miao; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Ecological impacts of the expansion of offshore wind farms on trophic level species of marine food chain - Lijing Wang; Bangguo Wang; Wenxi Cen; Rui Xu; Yuwei Huang; Xin Zhang; Yinghui Han; Yuanxun Zhang (Journal of Environmental Sciences, 2024)

Advances in chemical removal and degradation technologies for microplastics in the aquatic environment: A review - Tianhong Zhou; Shangjian Song; Rui Min; Xin Liu; Guozhen Zhang (Marine Pollution Bulletin, 2024)

Highly permeable nanofibrous polyamide membranes for multi-component wastewater treatment: Exploration of multiple separation mechanism - Rui Xin; Bingyin Jiang; Hongyang Ma; Ao Zhang; Madani Khan; Benjamin S. Hsiao (Journal of Environmental Chemical Engineering, 2024)

Mechanisms of benzene and benzo[a]pyrene biodegradation in the individually and mixed contaminated soils - Mukhtiar Ali; Qing Wang; Zhuanxia Zhang; Xing Chen; Min Ma; Zhiwen Tang; Rui Li; Biao Tang; Zhongyuan Li; Xiangfeng Huang; Xin Song (Environmental Pollution, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

Core-shell MOF@COF photocatalysts for synergistic enhanced U(VI) and tetracycline cleanup through space and carrier separation - Rui-Xiang Bi; Xin Liu; Lan Lei; Zhi-Hai Peng; Xiao-Xing Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Pharmacological inhibition of EZH2 using a covalent inhibitor suppresses human ovarian cancer cell migration and invasion - Lihong Shi; Qiangsheng Zhang; Shirui Zhu; Qing Tang; Xin Chen; Rui Lan; Ningyu Wang; Yongxia Zhu (Molecular and Cellular Biochemistry, 2024)

The Complete Genomic Sequence of Microbial Transglutaminase Producer, Streptomyces mobaraensis DSM40587 - Xi-long Feng; Rui-qi Zhang; Wei-ge Dong; Zhen-xin Wang; Jun-jie Xiao; Jing Wei; Jin-ming Gao; Jianzhao Qi (Biochemical Genetics, 2024)

Manganese disrupts the maturation and degradation of axonal autophagosome leading to hippocampal synaptic toxicity in mice via the activation of LRRK2 on phosphorylation of Rab10 - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Bin Xu (Science of The Total Environment, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Recovery hydrotalcite from neutralization sludge of acid mine drainage with high manganese for degradation of norfloxacin with activated peroxymonosulfate - Qingsheng Xu; Zhengbo Yue; Rui Deng; Kang Su; Xin Chuai; Kai Zhang; Jin Wang (Chemical Engineering Journal, 2024)

Occurrence characteristics and influencing factors of antibiotic resistance genes in rural groundwater in Henan Province - Kai Zhang; Kuangjia Li; Feiyue Hu; Rui Xin; Penglin Fan; Yarou Lu; Ningning Wang; Mengyuan Qin; Ruojing Li (Environmental Science and Pollution Research, 2024)

Effects of short and long-term thermal exposure on microbial compositions in soils contaminated with mixed benzene and benzo[a]pyrene: A short communication - Mukhtiar Ali; Xin Song; Qing Wang; Zhuanxia Zhang; Meng Zhang; Min Ma; Jilu Che; Rui Li; Xing Chen; Zhiwen Tang; Biao Tang; Xiangfeng Huang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Transport properties of oil-CO2 mixtures in calcite nanopores: Physics and machine learning models - Hongwei Zhang; Xin Wang; Qinjun Kang; Bicheng Yan; Shuyu Sun; Rui Qiao (Fuel, 2024)

Exploring the potential of a new marine bacterium associated with plastisphere to metabolize dibutyl phthalate and bis(2-ethylhexyl) phthalate by enrichment cultures combined with multi-omics analysis - Yueling Sun; Ying Zhang; Yongzheng Ma; Rui Xin; Xiaofeng Li; Zhiguang Niu (Environmental Pollution, 2024)

Progress in the Application of Microneedles in Eye Disorders and the Proposal of the Upgraded Microneedle with Spinule - Qiannan Yang; Tingting Zhang; Yujie Wu; Qianyue Liang; Wanqi Zhao; Rui Liu; Xin Jin (Pharmaceutical Research, 2024)

Risk assessment and source identification of soil heavy metals: a case study of farmland soil along a river in the southeast of a mining area in Southwest China - Huajian Chi; Xin Liu; Xiaofang Yang; Rui Zhang; Ting Xia; Yiping Sun; Kan Hu; Fangfang Hao; Yong Liu; Shengchun Yang; Qingwen Deng; Xiaodong Wen (Environmental Geochemistry and Health, 2024)

Effects of drought stress on seed germination and early seeding growth in Ferula ferulaeoides (Steud.) Korov. - Ying Ma; Kai Liao; Yun Zhu; Xin Lu; Kuan Wang; Xue Rui Zhang (Brazilian Journal of Botany, 2024)

Investigation of the antimicrobial susceptibility patterns of marine cyanobacteria in Bohai Bay: Cyanobacteria may be important hosts of antibiotic resistance genes in marine environment - Rui Xin; Ying Zhang; Kai Zhang; Yichen Yang; Yongzheng Ma; Zhiguang Niu (Science of The Total Environment, 2024)

Polysulfide regulation by defect-modulated Ta3N5− electrocatalyst toward superior room-temperature sodium-sulfur batteries - Zhen Zhang; Dan Luo; Jun Chen; Chuyin Ma; Matthew Li; Haoze Zhang; Renfei Feng; Rui Gao; Haozhen Dou; Aiping Yu; Xin Wang; Zhongwei Chen (Science Bulletin, 2024)

Degradation profile of environmental pollutant 17β-estradiol by human intestinal fungus Aspergillus niger RG13B1 and characterization of genes involved in its degradation - Qi-Meng Zhu; Chao Wang; Jing-Wen Liu; Rui Zhang; Xiu-Lan Xin; Juan Zhang; Cheng-Peng Sun; Xiao-Chi Ma (Journal of Hazardous Materials, 2024)

Estimation of the surface urban heat island intensity across 1031 global cities using the regression-modification-estimation (RME) method - Rui Yao; Xin Huang; Yongjun Zhang; Lunche Wang; Jiayi Li; Qiquan Yang (Journal of Cleaner Production, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Effects of Lacticaseibacillus paracasei SNB-derived postbiotic components on intestinal barrier dysfunction and composition of gut microbiota - Luyao Xiao; Changliang Zhang; Xueliang Zhang; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Research International, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Growth patterns and feeding characteristics in early developmental stages of Takifugu rubripes cultured in a recirculating aquaculture system - Xiaoqiang Gao; Shuquan Cao; Xianhong Zhang; Zhiwen Zhu; Chen Hai-Bin; Xing Rui; Kui-Feng Zhao; Chuan-Xin Zhang; Bao-Liang Liu (Aquaculture, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

The interaction among Kluyveromyces marxianus G-Y4, Lacticaseibacillus paracasei GL1, and Lactobacillus helveticus SNA12 and signaling molecule AI-2 participate in the formation of biofilm - Xiaomeng Wang; Kai Ma; Changliang Zhang; Feng Ji; Lili Chen; Xueliang Zhang; Ghahvechi Chaeipeima Mahsa; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Microbiology, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Development characteristics and failure modes of reactivated ancient landslides in the Sichuan–Tibet transportation corridor, China - Rui-an Wu; Yong-shuang Zhang; Chang-bao Guo; San-shao Ren; Xin Yao; Xiao-yi Liu; Zhi-hua Yang; Guo-liang Du (Journal of Mountain Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Enhanced As extraction from paddy soils with high As contamination risk by rice plant upon Si fertilization - Rui Huang; Xin Wang; Wei Wei; Yunhe Xie; Saihua Liu; Haoyu Chen; Renjie Zhang; Xionghui Ji (Chemosphere, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

Whole-genome analysis of the benzoic acid-degrading bacterium Bacillus halotolerans B28 to reveal its phytoprobiotic effects - Dandan Wang; Li Sun; Hong Yu; Chengkai Zhang; Xin Guan; Mengliang Wang; Rui Cheng; Chao Wang; Zhihong Xie (International Biodeterioration & Biodegradation, 2023)

Selenium speciation and volatile flavor compound profiles in the edible flowers, stems, and leaves of selenium-hyperaccumulating vegetable Cardamine violifolia - Yan Ma; Jinjing Yin; Jingyi Wang; Xin Liu; Jingren He; Rui Zhang; Shen Rao; Xin Cong; Yin Xiong; Muci Wu (Food Chemistry, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Dietary acetate promotes growth and nutrients deposition in Nile tilapia (Oreochromis niloticus) through increasing acetyl-CoA-triggered energy production - Wen-Hao Zhou; Samwel M. Limbu; Yuan Luo; Rui-Xin Li; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Anti-inflammatory metabolites from the fruits of Pittosporum elevaticostatum - Jun-Rui Ren; Xin-Zheng Liu; Wei-Zhen Kong; Zhao-Xuan Wang; Jin-Ming Gao; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Oxygen-exfoliated cobalt-doped C3N4 for superior Fenton-like catalysis: The accessible metal exposure and synergistic pollutant adsorption from three-dimensional layered configuration - Qi-Xin Wei; Ai-Yong Zhang; Zedong Yang; Song Hu; De-Jin Wang; Chi Zhang; Chang Liu; Rui Liu (Journal of Environmental Chemical Engineering, 2023)

Process and mechanism of recovering layered double hydroxides (LDHs) from acid mine drainage (AMD) and synergetic removal of manganese - Qingsheng Xu; Zhengbo Yue; Rui Deng; Xinquan Wang; Xin Chuai; Kai Zhang; Jin Wang (Journal of Environmental Chemical Engineering, 2023)

Application of a novel phage LPCS28 for biological control of Cronobacter sakazakii in milk and reconstituted powdered infant formula - Geng Zou; Libère Ndayishimiye; Lingxiang Xin; Manshan Cai; Longjian Zhang; Jie Li; Zhiyong Song; Renwei Wu; Yang Zhou; Yuanguo Shi; Yingwang Ye; Rui Zhou; et al. (Food Research International, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Effects of Lactiplantibacillus plantarum with different phenotypic features on the nutrition, flavor, gel properties, and digestion of fermented soymilk - Xueliang Zhang; Changliang Zhang; Luyao Xiao; Suying Wang; Xiaochan Wang; Kai Ma; Feng Ji; Elham Azarpazhooh; Marjan Ajami; Xin Rui; Wei Li (Food Bioscience, 2023)

mARC dependent NO synthesis activates CanA-Relish-AMPs signal pathway in Eriocheir sinensis during nitrite stress - Rui Jia; Liangmin Zheng; Lihua Zhang; Xin Huang; Qian Ren (Fish & Shellfish Immunology, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of hypoxia on the gill morphological structure, apoptosis and hypoxia-related gene expression in blunt snout bream (Megalobrama amblycephala) - Xin-xin Yu; Yan-rui Zhang; Shan-shan Li; Guo-dong Zheng; Shu-ming Zou (Fish Physiology and Biochemistry, 2023)

Analysis of the Interannual Variability of Pacific Swell Pools - Xin Zhang; Kejian Wu; Rui Li; Dongze Li; Shuai Zhang; Ruyan Zhang; Shuo Li; Xianghui Dong (Journal of Marine Science and Engineering, 2023)
The investigation of the propagation of swells throughout the ocean has long been a subject of significant interest in physical oceanography. This paper investigates the interannual variability of the Pacific swell pools and examines the factors contributing to their formation using the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA5 re-analysis dataset. Our results show that the interaction between swell propagation and wind fields influences the formation and development of Pacific swell pools. The eastern and southern Pacific swell pools are mainly caused by the northward propagation of swells from the South Pacific; the western and northern swell pools are primarily influenced by the southward propagation of swells from the North Pacific; and the central part of the swell pools is the result of the combined impact of both swell propagation from the north and south Pacific. The size of the swell pools in the Pacific Ocean is at its maximum in the northern hemisphere during the winter (December, January, and February) and at its minimum during the summer (June, July, and August). Due to the impact of the low-pressure systems, the swell pools in the winter hemisphere are relatively small, while the swell pools in the summer hemisphere are significantly larger. There is a relationship between the swell pools and ENSO events. When an El Niño event (La Niña event) occurs, the swells propagating to the low latitudes of the Pacific Ocean from high latitudes will strengthen (weaken), resulting in an increase (decrease) in the size of the swell pools. Analyzing the spatial and temporal distribution of the swell pools is important for understanding the large-scale effect of waves.

Relationship between Large-Scale Variability of North Pacific Waves and El Niño-Southern Oscillation - Xin Zhang; Kejian Wu; Rui Li; Shuai Zhang; Ruyan Zhang; Jin Liu; Alexander V. Babanin (Journal of Marine Science and Engineering, 2023)
Ocean waves are crucial for driving various oceanic processes. In this study, the spatial and temporal distribution of significant wave height (SWH) in the North Pacific (NP) is analyzed using the 42-year ERA5 reanalysis dataset from European Centre for Medium-Range Weather Forecasts (ECMWF). The presence of an ENSO signal is confirmed in wave fields of the North Pacific. Furthermore, the spatial distributions of swells and wind waves are analyzed using the Empirical Orthogonal Function (EOF) method, revealing that waves can transport large-scale signals from the NP to lower latitudes through swells. In addition, our research reveals a relationship between ENSO and Stokes drift in the NP. Stokes drift contributes positively to the maintenance of stable sea surface temperatures (SSTs) by transporting more (less) water towards the equatorial Pacific during El Niño (La Niña year) years. It is further noted that during strong ENSO events, the strength of the Stokes drift anomaly intensifies accordingly, which implies a strong link between wave-induced transport and ENSO.

Vegetation descriptors from Sentinel-1 SAR data for crop growth monitoring - Xin Bao; Rui Zhang; Jichao Lv; Renzhe Wu; Hongsheng Zhang; Jie Chen; Bo Zhang; Xiaoying Ouyang; Guoxiang Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Trehalose metabolism targeting as a novel strategy to modulate acid tolerance of yeasts and its application in food industry - Zhongpeng Guo; Moying Li; Zitao Guo; Rui Zhu; Yu Xin; Zhenghua Gu; Liang Zhang (Food Microbiology, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Ru-catalyzed chemoselective methoxycarbonylation of methyl pentenoate: An assistant role of chloride anions - Shu Zhang; Rui Sun; Pengxin Guan; Yaofeng Wang; Ling Wang; Yanli Zhu; Lijun Han; Jiayu Xin (Chemical Engineering Journal, 2023)

Contrasting the effect of aerosol properties on the planetary boundary layer height in Beijing and Nanjing - Xin Huang; Yuying Wang; Yi Shang; Xiaorui Song; Rui Zhang; Yuxiang Wang; Zhanqing Li; Yuanjian Yang (Atmospheric Environment, 2023)

Transcriptome Analysis of the Mouse Medial Prefrontal Cortex in a Chronic Constriction Injury Model - Qi-Min Zheng; Zi-Rui Zhou; Xin-Yu Hou; Ning Lv; Yu-Qiu Zhang; Hong Cao (NeuroMolecular Medicine, 2023)

Transient analyses for China initiative Accelerator Driven System using the extended BELLA code - Guan Wang; Janne Wallenius; Rui Yu; Wei Jiang; Lu Zhang; Xin Sheng; Di Yun; Long Gu (Annals of Nuclear Energy, 2023)

Refined feature fusion for in-field high-density and multi-scale rice panicle counting in UAV images - Yao Chen; Rui Xin; Haiyan Jiang; Yonghuai Liu; Xiaoqi Zhang; Jialin Yu (Computers and Electronics in Agriculture, 2023)

Localized host-rock porosity near sealed fractures at 7 km depth: Geochemical evidence of deep-seated porosity controls - Denglin Han; Jizhen Zhang; Chenchen Wang; Wei Lin; Rui Yuan; Xin Nie; Juan Zhang (Journal of Structural Geology, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Controlled release of Lactiplantibacillus plantarum by colon-targeted adhesive pectin microspheres: Effects of pectin methyl esterification degrees - Danling Xu; Xiaogan Zhao; Ghahvechi Chaeipeima Mahsa; Kai Ma; Changliang Zhang; Xin Rui; Mingsheng Dong; Wei Li (Carbohydrate Polymers, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Co-cultivation effects of Lactobacillus helveticus SNA12 and Kluveromyces marxiensis GY1 on the probiotic properties, flavor, and digestion in fermented milk - Xiaomeng Wang; Wenpei Li; Ghahvechi Chaeipeima Mahsa; Changliang Zhang; Kai Ma; Xin Rui; Wei Li (Food Research International, 2023)

One-dimensional self-weight consolidation of layered soil under variable load and semi-permeable boundary condition - Hong-Xin Chen; Shi-Jin Feng; Zhang-Wen Zhu; Liang Gao; Zhang-Long Chen; Shu-Rui Wang (Computers and Geotechnics, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

ROS and DRP1 interactions accelerate the mitochondrial injury induced by polystyrene nanoplastics in human liver HepG2 cells - Yunjing Li; Menghao Guo; Shuyan Niu; Mengting Shang; Xiaoru Chang; Zuoyi Sun; Rui Zhang; Xin Shen; Yuying Xue (Chemico-Biological Interactions, 2023)

The increasing risk of future simultaneous droughts over the Yangtze River basin based on CMIP6 models - Ying Zhang; Xin Hu; Zengxin Zhang; Rui Kong; Zhenhua Peng; Qi Zhang; Xi Chen (Stochastic Environmental Research and Risk Assessment, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Study on dynamic fracture growth mechanism of continental shale under compression failure - Siwei Meng; Dongxu Li; Xin Liu; Zihan Zhang; Jiaping Tao; Liu Yang; Zhenhua Rui (Gas Science and Engineering, 2023)

Solid-state fermentation alters the fate of red kidney bean protein during buccal and gastrointestinal digestion: Relationship with cotyledon cell wall integrity - Wenjing Sun; Jie He; Haijun Wang; Qiuqin Zhang; Wei Li; Xin Rui (Food Chemistry, 2023)

Hippocampus: Molecular, Cellular, and Circuit Features in Anxiety - Hu-Jiang Shi; Shuang Wang; Xin-Ping Wang; Rui-Xin Zhang; Li-Juan Zhu (Neuroscience Bulletin, 2023)

Causal associations of circulating Helicobacter pylori antibodies with stroke and the mediating role of inflammation - Xingzhi Guo; Peng Tang; Xin Zhang; Rui Li (Inflammation Research, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Thermal and nonthermal effect of microwave irradiation on the pore microstructure and hydrocarbon generation of organic matter in shale - Min Wang; Yuchen Zhang; Jinbu Li; Rui Ma; Xin Wang; Ying Li; Haoming Shao; Jinxu Zhang; Junsheng Fei; Zixiao Deng; Baoxin Pan (Marine and Petroleum Geology, 2023)

Highly reactive coke made from Low-rank Coal: Relationship between thermal properties and multilevel structure - Xin Zhang; Jun Zhang; Rui Guo; Qiang Xiao; Yawei Feng; Huan Cheng (Fuel, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

Immediate and long-term changes in the epidemiology, infection spectrum, and clinical characteristics of viral and bacterial respiratory infections in Western China after the COVID-19 outbreak: a modeling study - Tianshan Shi; Xin Zhao; Xiaoshu Zhang; Lei Meng; Donghua Li; Xinfeng Liu; Hongmiao Zheng; Deshan Yu; Tingrong Wang; Rui Li; Juansheng Li; Xiping Shen; et al. (Archives of Virology, 2023)

Characteristics, sources and health risk assessment of atmospheric carbonyls during multiple ozone pollution episodes in urban Beijing: Insights into control strategies - Yunfeng Li; Hong Li; Xin Zhang; Yuanyuan Ji; Rui Gao; Zhenhai Wu; Manfei Yin; Lei Nie; Wei Wei; Guohao Li; Yafei Wang; Mei Luo; et al. (Science of The Total Environment, 2023)

Assessment of dynamic digestion fate of soy protein gel induced by lactic acid bacteria: A protein digestomics research - Yaqiong Wang; Wenjing Sun; Yi Zhang; Wei Li; Qiuqin Zhang; Xin Rui (Food Hydrocolloids, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

The circadian regulation of extracellular ATP - Xin Wang; Yu-Ting Dong; Xiu-Ming Hu; Ji-Zhou Zhang; Nan-Rui Shi; Yan-Qin Zuo; Xu Wang (Purinergic Signalling, 2023)
Extracellular ATP is a potent signaling molecule released from various cells throughout the body and is intimately involved in the pathophysiological functions of the nervous system and immune system by activating P2 purinergic receptors. Recent increasingly studies showed that extracellular ATP exhibits circadian oscillation with an approximately 24-h periodicity, which participates in regulatory pathways of central oscillator suprachiasmatic nucleus and peripheral oscillator bladder, respectively. Oscillators modulate the protein expression of ATP release channels and ectonucleotidase activity through clock genes; indeed, real-time alterations of ATP release and degradation determine outcomes of temporal character on extracellular ATP rhythm. The regulatory pathways on extracellular ATP rhythm are different in central and peripheral systems. In this review, we summarize the circadian rhythm of extracellular ATP and discuss several circadian regulatory pathways in different organs via ATP release and degradation, to provide a new understanding for purinergic signaling in the regulatory mechanism of circadian rhythm and a potential target to research the circadian regulation of extracellular ATP in other circadian oscillators.

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

Dietary sodium acetate improves high-fat diet utilization through promoting differential nutrients metabolism between liver and muscle in Nile tilapia (Oreochromis niloticus) - Wen-Hao Zhou; Samwel M. Limbu; Rui-Xin Li; Yuan Luo; Jiong Ren; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Aquaculture, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

How seasonality affects the environmental performance of fresh appetite: Insights from cherry consumption in China - Xin Xiong; Junyi Shen; Yan Hao; Lixiao Zhang; Rui Zhao; Shoujuan Tang; Xinqing Li; Zhimin Shi (Journal of Environmental Management, 2023)

Associations of co-exposure to polycyclic aromatic hydrocarbons and metals with hyperuricemia risk in Chinese coke oven workers: Mediating roles of oxidative damage - Chaofan Guo; Xin Liu; Xiaojing Liao; Haimei Wu; Zhaorui Zhang; Dehua Wu; Rui Ma; Yongshun Huang; Na Zhao; Yongmei Xiao; Qifei Deng (Environmental Pollution, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The formation of supercritical carbon dioxide hydrothermal vents in the Okinawa Trough - Fanfan Tian; Rui Li; Guozhi Xie; Kun Wang; Lipeng Zhang; Xin Zhang; Weidong Sun (Science Bulletin, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Rural residents' climate change perceptions, personal experiences, and purchase intention–behavior gap in energy-saving refrigeration appliances in Southwest China - Rui He; Jianjun Jin; Xin Qiu; Chenyang Zhang; Jubo Yan (Environmental Impact Assessment Review, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Boosting elementary steps kinetics towards energetic alkaline hydrogen evolution via dual sites on phase-separated Ni–Cu–Mn/hydroxide - Zhimin Li; Sisi Xin; Yirong Zhang; Zhengfu Zhang; Chengping Li; Caiju Li; Rui Bao; Jianhong Yi; Mingli Xu; Jinsong Wang (Chemical Engineering Journal, 2023)

Yeast cell wall polysaccharides in Tibetan kefir grains are key substances promoting the formation of bacterial biofilm - XiaoMeng Wang; XueLiang Zhang; YuKe Wang; NanYu Tang; LuYao Xiao; JuanJuan Tian; Xin Rui; Wei Li (Carbohydrate Polymers, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Effects of coexposure to noise and mixture of toluene, ethylbenzene, xylene, and styrene (TEXS) on hearing loss in petrochemical workers of southern China - Yan Zhang; Yan Liu; Zongxin Li; Xin Liu; Qingfei Chen; Jingyao Qin; Qilong Liao; Rui Du; Qifei Deng; Yongmei Xiao; Xiumei Xing (Environmental Science and Pollution Research, 2022)

Insight into enhanced degradation of tetracycline over peroxymonosulfate activated via biochar-based nanocomposite: performance and mechanism - Tiehong Song; Yanjiao Gao; Jian Ye; Xin Zhang; Rui Su; Jiacheng Luo (Environmental Science and Pollution Research, 2022)

Comparison of horizontal wind observed by wind profiler radars with ERA5 reanalysis data in Anhui, China - Xueliang Deng; Dongyan He; Guangyuan Zhang; Song Zhu; Rui Dai; Xiaolong Jin; Wei Fu; Weiwei Shen; Jian Chen; Yuxiang Fan; Chunxuan Wei; Xin Li (Theoretical and Applied Climatology, 2022)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Characterizing diversity based on phenotypes and molecular marker analyses of purple yam (Dioscorea alata L.) germplasm in southern China - Xin Chen; Jingyu Sun; Qianglong Zhu; Yao Xiao; Hongyu Zhang; Yingjin Huang; Putao Wang; Tianxu Cao; Rui Hu; Zijin Xiang; Nan Shan; Qinghong Zhou (Genetic Resources and Crop Evolution, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Genotypic variations in GST genes reveal a regulatory role in the accumulation of caffeoylquinic acids in leafy sweet potato (Ipomoea batatas) - Deka Reine Judesse Soviguidi; Yi Liu; Rui Pan; Salah Fatouh Abou-Elwafa; Wen-Ying Zhang; Xin-Sun Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Long non-coding RNA RPL34-AS1 ameliorates oxygen–glucose deprivation-induced neuronal injury via modulating miR-223–3p/IGF1R axis - Xin-ya Wei; Tian-qi Zhang; Rui Suo; You-yang Qu; Yan Chen; Yu-lan Zhu (Human Cell, 2022)

A Realistic and Integrated Model for Evaluating Offshore Oil Development - Rui Qiu; Zhuochao Li; Qin Zhang; Xin Yao; Shuyi Xie; Qi Liao; Bohong Wang (Journal of Marine Science and Engineering, 2022)
With the rising consumption of oil resources, major oil companies around the world have increasingly engaged in offshore oil exploration and development, and offshore oil resources have accounted for an increasing proportion. Offshore oil engineering projects are capital intensive, and the development of offshore oil fields faces a tough battle, especially in a period of low oil prices. Thus, a comprehensive evaluation model is highly needed to help assess economic benefits and provide meaningful and valuable information for operators and investors to make sensible decisions. This study firstly proposed a realistic and integrated evaluation model for offshore oil development based on actual historical project data. This evaluation model incorporated modules from the underwater system to the platform system and processes from oil reservoir extraction to oil, gas and water treatment. The uncertain parameters in the evaluation process are dealt with by sensitivity analysis and Monte Carlo simulation. The proposed model is applied to a typical offshore oil development project in Bohai Bay, China. The results reveal that the recovery factor and oil price have the greatest impact on the economic benefits. In the case of deterministic analysis, the breakeven oil price of the project is 40.59 USD/bbl. After considering the uncertainty of project parameters, the higher the oil price, the greater the probability of NPV > 0. When the oil price is higher than 70 USD/bbl, even with uncertain project parameters, the probability of NPV > 0 can still be as high as 97.39%.

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

High-Frequency Repetitive Transcranial Magnetic Stimulation Regulates Astrocyte Activation by Modulating the Endocannabinoid System in Parkinson’s Disease - Xin Kang; Bing Zhang; Wanqing Du; Rui Zhao; Xuedong Liu; Ya Bai; Xiaobing Jiang; Jie Pang; Chenguang Zhao; Xiang Mou; Fang Gao; Hua Yuan; et al. (Molecular Neurobiology, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Genome-wide analysis and expression pattern of the PIN gene family during Korla fragrant pear calyx development - Min Jin; Xin Gong; Qiang Zhang; Yan Chen; Hongyu Ma; Tianzheng Zhang; Cuiyun Wu; Rui Zhang; Qi Zhang; Shutian Tao; Jianping Bao (Acta Physiologiae Plantarum, 2022)

Distribution Analysis of Local Ice Pressures in the Indentation Test at Various Velocities - Guojun Wang; Qianjin Yue; Dayong Zhang; Yanghua Fu; Xin Peng; Rui Dong (Journal of Marine Science and Engineering, 2022)
When sea ice acts on vertical structures, there are much higher pressures in localized areas known as high-pressure zones (HPZs) than in other areas. The damage failure mode of sea ice varies with the sea ice velocity and affects the distribution of HPZs. In this study, an indentation test that drives ice sheet interaction with a vertical rigid plate (indentor) was designed, and a pressure sensor (consisting of 32 × 32 small pressure units of 100 mm2) was installed on the indentor face to measure the local ice pressure (LIP) at various velocities. The distribution of the LIPs along the ice thickness, the probability distribution of the LIPs and the distribution relationship of the LIPS in space and time were obtained from the measurement. The results show that the LIPs were mainly distributed in the middle of the sea ice, which is consistent with full-scale observations and previous research. Ductile failure of the sea ice results in a larger LIP distribution area than brittle failure at the same threshold kt (kt = σL/σcr). The probability distribution of the LIPs decreases exponentially with increasing pressure and follows a lognormal distribution. The maximum LIP appears at the peak moment of the global force when the sea ice failure mode is mainly ductile failure. However, the maximum LIP may not occur at the peak moment when the sea ice failure is mainly brittle failure and, instead can appear at any moment in the global force time history curve. The HPZ (which is larger than 7/8 times the maximum LIP) area is less than 2% of the nominal contact area at various velocities. The influence of the sea ice velocity on the spatial and temporal distribution of LIP is analyzed, and the results provide a reference for designing structures with local strength in ice regions.

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

SSR analysis and fingerprint construction to evaluate the genetic diversity of medicinal plum varieties - Rui Wang; Xin Li; Wei Zhang; Jinmei Ou; Chengwu Fang; Qianqian Song; Huiyin Zhou (Journal of Plant Biochemistry and Biotechnology, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Numerical simulation study on the seepage characteristics of coal seam infusion effected by mining-induced stress - Yanbin Yu; Qilin Xin; Weimin Cheng; Jun Rui; Xin Zhang (Bulletin of Engineering Geology and the Environment, 2021)

Mechanism of environmental factors regulating water consumption of Larix gmelinii forests - Xin Zhang; Qiuliang Zhang; Zhihong Xu; Rui Wang; Yanan Jian; Jingfu Yang; Changlei Sun; Jiafu Wang (Journal of Soils and Sediments, 2021)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Clarification of the etiology of peach bacteria leaf shot hole caused by Pantoea spp. in Henan Province, China, based on morphological characteristics and multi-locus sequences analysis - Rui Zang; Lu-lu Song; Chao Xu; Xin-ming Yin; Zhan-xiang Qiao; Yue-hua Geng; Meng Zhang (European Journal of Plant Pathology, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Ca2+/Calmodulin-NOS/NO-TNFs Pathway Hallmarks the Inflammation Response of Oyster During Aerial Exposure - Hao Chen; Lusheng Xin; Lin Wang; Huan Zhang; Rui Liu; Hao Wang; Xue Qiao; Lingling Wang; Linsheng Song (Frontiers in Marine Science, 2021)
Aerial exposure (emersion) due to the periodical ebb and flow of tides is a major stressor for intertidal organisms and a key environmental factor in shaping their local communities. Oysters are among the most emersion-tolerant mollusk species and can survive for several days under aerial exposure. Noticeably, overwhelming inflammation responses could occur during the emersion stress. However, mechanisms beneath the activation and modulation of emersion-induced inflammation response have remained largely unknown. Ca 2+ is an important intracellular second messenger that plays indispensable roles in inflammation response by cooperation with calmodulin (CaM) genes. Here, we showed that intracellular Ca 2+ accumulates rapidly in oyster hemocytes during emersion stress along with the changes in the protein levels of three CaM genes, which function as intracellular sensors of Ca 2+ . As downstream effector of Ca 2+ /CaM complex, nitric oxide synthase (NOS) activity in hemocytes was enhanced during the emersion stress, facilitating a greater production of nitrite oxide (NO). Augmentation of NO concentration was associated with the increased mRNA expression levels of two oyster cytokines (CgTNFs) during aerial exposure. The robust accumulation of cytokines and severe injury of tissues in oysters have been regarded as potential cause and marker of their death in prolonged emersion stress. Here, both the expression levels of CgTNFs and the tissue injuries of oysters were attenuated when Ca 2+ /CaM complex or NOS activity were repressed in vivo during the emersion stress. These findings indicate that Ca 2+ /CaM-NOS/NO-CgTNFs pathway is critically involved in the emersion-induced inflammation response in oysters and plays a role in the resistance against long-term aerial exposure.

High-resolution Simulation of an Extreme Heavy Rainfall Event in Shanghai Using the Weather Research and Forecasting Model: Sensitivity to Planetary Boundary Layer Parameterization - Rui Wang; Yiting Zhu; Fengxue Qiao; Xin-Zhong Liang; Han Zhang; Yang Ding (Advances in Atmospheric Sciences, 2021)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Neurofeedback Training for Brain Functional Connectivity Improvement in Mild Cognitive Impairment - Xin Li; Jie Zhang; Xiang-Dong Li; Wei Cui; Rui Su (Journal of Medical and Biological Engineering, 2020)

Genetic variants in Ras/Raf/MEK/ERK pathway are associated with gastric cancer risk in Chinese Han population - Xiaowei Wang; Xu Wu; Junyi Xin; Shuwei Li; Rui Zheng; Dan Guan; Weida Gong; Qinghong Zhao; Meilin Wang; Haiyan Chu; Mulong Du; Guoquan Tao; et al. (Archives of Toxicology, 2020)

Candidate proteins involved in the calyx abscission process of ‘Kuerlexiangli’ (Pyrus sinkiangensis Yu) identified by iTRAQ analysis - Xin Gong; Jianping Bao; Jing Chen; Kaijie Qi; Zhihua Xie; Weikang Rui; Guowei Hao; Katsuhiro Shiratake; Shahrokh Khanizadeh; Shaoling Zhang; Shutian Tao (Acta Physiologiae Plantarum, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Development of Ultra-sensitive Method for Determination of Trace Atrazine Herbicide in Environmental Water Using Magnetic Graphene Oxide-Based Solid-Phase Extraction Coupled with Dispersive Liquid-Liquid Microextraction Prior to Gas Chromatography-Mass Spectrometry - Xiaojun Zhang; Xiaoguo Ma; Xin Li; Chunying Li; Rui Wang; Meiqin Chen (Water, Air, & Soil Pollution, 2018)

Transformations of 2-line ferrihydrite and its effect on cadmium adsorption - Yi Huang; Shipeng Zhang; Chao Liu; Huilin Lu; Shijun Ni; Xin Cheng; Zhijie Long; Rui Wang (Environmental Science and Pollution Research, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Screening HCV genotype-specific epitope peptides based on conserved sequence analysis and B cell epitope prediction in HCV E2 region - Rui Hua; Xiaoyu Jiang; Lingxia Qi; Shanshan Guan; Ziyu Kuai; Yongbo Qiao; Yan Xu; Xin Gong; Yuhua Shi; Wei Kong; Junqi Niu; Hao Zhang; et al. (Immunologic Research, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

A new cinnamic acid glycoside from roots of Heracleum dissectum - Zhi-Gang Wang; Jie Mi; Xin-Rui Wang; Ya-Yu Huo; Ya-Jie Peng; Hai-Min Zhang; Yang Gao; Hai-Long Zhang (Natural Product Research, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Inhibitory effect of StCYP707A1 gene on tuberization in transgenic potato - Lu Liu; Rui-Jie Zhang; Wen-Jiao Zhu; Xin-Ru Liu; Ke Shi; Min Chen; Qing Yang (Plant Biotechnology Reports, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Phytotoxicity of CeO2 nanoparticles on radish plant (Raphanus sativus) - Xin Gui; Mengmeng Rui; Youhong Song; Yuhui Ma; Yukui Rui; Peng Zhang; Xiao He; Yuanyuan Li; Zhiyong Zhang; Liming Liu (Environmental Science and Pollution Research, 2017)

Morphological and molecular identification of Habronema spp. (Nematoda: Habronematidae) from donkeys in Xinjiang, China, and notes on the taxonomical status of Habronema majus (Creplin, 1849) and H. microstoma (Schneider, 1866) - Rui Jian; Shi-Wei Wang; Wei-Xin Zhang; Lu-Ping Zhang (Systematic Parasitology, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

The transgenic expression of human follistatin-344 increases skeletal muscle mass in pigs - Fei Chang; Rui Fang; Meng Wang; Xin Zhao; Wen Chang; Zaihu Zhang; Ning Li; Qingyong Meng (Transgenic Research, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Variations of Nutrients in Gross Rainfall, Stemflow, and Throughfall Within Revegetated Desert Ecosystems - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (Water, Air, & Soil Pollution, 2016)

MicroRNA-1228* inhibit apoptosis in A549 cells exposed to fine particulate matter - Xiaobo Li; Zhen Ding; Chengcheng Zhang; Xin Zhang; Qingtao Meng; Shenshen Wu; Shizhi Wang; Lihong Yin; Yuepu Pu; Rui Chen (Environmental Science and Pollution Research, 2016)

Optimization of operation conditions for the mitigation of nitrous oxide (N2O) emissions from aerobic nitrifying granular sludge system - Rui-Ting Liu; Xin-Hua Wang; Yan Zhang; Ming-Yu Wang; Ming-Ming Gao; Shu-Guang Wang (Environmental Science and Pollution Research, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

Variation analysis of pathogenic Vibrio spp. and Pseudomonas spp. in Changhai mollusc farming waters using real-time PCR assay during 2011–2014 - Rui Liu; Limei Qiu; Xin Zhao; Huan Zhang; Lingling Wang; Zhanhui Hou; Dahai Gao; Linsheng Song (Marine Biology Research, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Comparison of diurnal dynamics in evaporation rate between bare soil and moss-crusted soil within a revegetated desert ecosystem of northwestern China - Ya-Feng Zhang; Xin-Ping Wang; Yan-Xia Pan; Rui Hu (Journal of Earth System Science, 2016)

First survey of parasitic helminths of goats along the Han River in Hubei Province, China - Xin Yang; Robin B. Gasser; Rui Fang; Jinrong Zeng; Kaixiang Zhu; Mingwei Qi; Zongze Zhang; Li Tan; Weiqiang Lei; Yanqin Zhou; Junlong Zhao; Min Hu (Acta Parasitologica, 2016)
Diseases caused by parasitic helminths cause considerable production and economic losses in livestock worldwide. Understanding the epidemiology of these parasites has important implications for controlling them. The main purpose of the present study was to estimate the prevalence of key parasitic helminths in goats along the Han River in Zhanggang, Hubei Province (from January to December 2014). We used faecal flotation and sedimentation techniques as well as PCR-based DNA sequencing to detect and identify helminths. Results showed that the prevalence of helminths was high throughout the year, particularly for gastrointestinal nematodes. These first findings provide useful baseline information for goat helminths in Zhanggang, and a starting point for the implementation of control programs. With an increased expansion of the goat industry in China, the findings also emphasise the need to undertake prevalence surveys in other regions of China where extensive farming practices are used.

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Diagnosis of Small Bowel Obstruction using Targeted Enterography During Nasointestinal Decompression - Rui-hong Li; De-chun Li; Qin-zhong Tian; Ping Wu; Xin-hui Zhang (Cell Biochemistry and Biophysics, 2015)

Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells - Xin-ping Liang; Dong-qiang Zhang; Yan-yan Chen; Rui Guo; Jie Wang; Cheng-zhang Wang; Ying-hua Shi (Journal of Zhejiang University-SCIENCE B, 2015)

Characterization of genomic sequence of a drought-resistant gene TaSnRK2.7 in wheat species - HONG YING ZHANG; WEI LI; XIN GUO MAO; RUI LIAN JING (Journal of Genetics, 2015)

Village network centrality in rural tourism destination: A case from Yesanpo tourism area, China - Rui-ying Zhang; Jian-chao Xi; Shou-kun Wang; Xin-ge Wang; Quan-sheng Ge (Journal of Mountain Science, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Dependence of shrub canopy water storage on raindrop size in revegetated desert - Xin-ping Wang; Hao Zhang; Ya-feng Zhang; Rui Hu; Yan-xia Pan (Hydrological Sciences Journal, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Potential impact of climate change on future water demand in Yulin city, Northwest China - Wang Xiao-jun; Zhang Jian-yun; Shahid Shamsuddin; He Rui-min; Xia Xing-hui; Mou Xin-li (Mitigation and Adaptation Strategies for Global Change, 2015)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Gabapentin Enhances the Morphine Anti-Nociceptive Effect in Neuropathic Pain via the Interleukin-10-Heme Oxygenase-1 Signalling Pathway in Rats - Yu-Hua Bao; Quan-Hong Zhou; Rui Chen; Hao Xu; Lu-Lu Zeng; Xin Zhang; Wei Jiang; Dong-Ping Du (Journal of Molecular Neuroscience, 2014)

Ecto-Mesenchymal Stem Cells from Facial Process: Potential for Muscle Regeneration - Xin Nie; Yongjun Xing; Manjin Deng; Li Gang; Rui Liu; Yongjie Zhang; Xiujie Wen (Cell Biochemistry and Biophysics, 2014)

Consumption of hydrogen-rich water alleviates renal injury in spontaneous hypertensive rats - Hai-Guang Xin; Bei-Bei Zhang; Zhi-Qin Wu; Xiao-Feng Hang; Wen-Sheng Xu; Wu Ni; Rui-Qi Zhang; Xiao-Hui Miao (Molecular and Cellular Biochemistry, 2014)

Precise and Economical Dredging Model of Sediments and Its Field Application: Case Study of a River Heavily Polluted by Organic Matter, Nitrogen, and Phosphorus - Rui Zhang; Fan-Xin Zeng; Wu-Jun Liu; Raymond J. Zeng; Hong Jiang (Environmental Management, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Condensation of water vapour on moss-dominated biological soil crust, NW China - XIN-PING WANG; YAN-XIA PAN; RUI HU; YA-FENG ZHANG; HAO ZHANG (Journal of Earth System Science, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)

Overexpression of PeHSF mediates leaf ROS homeostasis in transgenic tobacco lines grown under salt stress conditions - Zedan Shen; Mingquan Ding; Jian Sun; Shurong Deng; Rui Zhao; Meijuan Wang; Xujun Ma; Feifei Wang; Huilong Zhang; Zeyong Qian; Yue Hu; Rui Yu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Heterogeneity of soil surface temperature induced by xerophytic shrub in a revegetated desert ecosystem, northwestern China - YA-FENG ZHANG; XIN-PING WANG; YAN-XIA PAN; RUI HU; HAO ZHANG (Journal of Earth System Science, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Diurnal and seasonal variations of surface albedo in a spring wheat field of arid lands of Northwestern China - Ya-feng Zhang; Xin-ping Wang; Yan-xia Pan; Rui Hu (International Journal of Biometeorology, 2013)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Water resources management strategy for adaptation to droughts in China - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Amgad ElMahdi; He Rui-min; Bao Zhen-xin; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Gini coefficient to assess equity in domestic water supply in the Yellow River - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Amgad ElMahdi; Rui-min He; Xin-gong Wang; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

3′UTR-Dependent Localization of a Purkinje Cell Messenger RNA in Dendrites - Rui Zhang; Xulun Zhang; Feng Bian; Xin-an Pu; Karl Schilling; John Oberdick (The Cerebellum, 2008)

Survival and integration of tissue-engineered corneal stroma in a model of corneal ulcer - Chao Zhang; Xin Nie; Dan Hu; Yuan Liu; Zhihong Deng; Rui Dong; YongJie Zhang; Yan Jin (Cell and Tissue Research, 2007)

The effects of flooding on several hybrid poplar clones in Northern China - Ji-Rui Gong; Xin-Shi Zhang; Yong-Mei Huang; Chun-Lai Zhang (Agroforestry Systems, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)